Pulmonary Artery Aneurysm (PAA) in Behçet's Disease Presenting With Recurrent Hemoptysis: A Case Report - Shahabaldin Sorouri; Maryam Safari Farmad; Amirhossein Amiriani; Amir Baniasad (Clinical Case Reports)
ABSTRACT Pulmonary artery aneurysm is a serious but under‐recognized complication of Behçet's disease that may present with hemoptysis. Early diagnosis coupled with timely initiation of immunosuppressive therapy is crucial in preventing aneurysmal progression and associated life‐threatening complications.